Pola Genangan Air (Banjir) DAS Sekanak-Lambidaro - Raden Muhammad Edwar; Achmad Syarifudin (CV. Syntax Corporation Indonesia, 2021)
Flood is a common problem that occurs in parts of Indonesia. The Musi River and nineteen drainage systems in the city of Palembang that serve different cathment area units contribute to flood disasters each year. The effect of maximum discharge on the level of flood vulnerability is the continuation factor of land use results and (1) rainfall in addition to (2) tides that usually occur periodically on the Musi river. At high water velocities, it is fast and the amount of water is small, resulting in a high flow of water so that the flow is very heavy and has a destructive impact. The old paradigm for the construction of drainage channels or subdas was to channel water runoff to the nearest canal / water body so that it canreach the downstream faster. This paradigm is no longer suitable with current conditions where the flow of flowing water must be held longer by being infiltrated into the ground through water catchment areas such as infiltration wells, retention ponds, reservoirs and so on so that water does not immediately reach the downstream to maintain water supplies. The drainage system of Palembang City follows the natural drainage system pattern, because the drainage system is the main drain of the existing drainage zone, while the distribution of the drainage loading area is adjusted to the direction of the existing drainage flow (ESP-USAID, 2009). Drainage or Musi subdas in several areas in Palembang City which are water catchment areas that have changed their function into residential areas and with untreated drainage systems, narrowing of channels, silting and accumulation of garbage in drainage and puddles due to the capacity of primary drainage being exceeded so that at some time lately there has been frequent inundation and flooding during periodic rains and tides